Case report: Trigeminal neuralgia misdiagnosed as glossopharyngeal neuralgia - Wu, Liangzhe; Xiong, Jinbiao; Huang, Ying; Han, Kunning; Cai, Kunhao; Fu, Xuejun (Frontiers in Neurology, 2023)
Background： Both trigeminal neuralgia and glossopharyngeal neuralgia are cranial neuralgias with the same clinical manifestation, pathological features, and trigger factors, as well as overlapping pain locations of the two groups of nerves. Relying on magnetic resonance imaging examination alone, it is easy to misdiagnosis. Case presentation： A 72-year-old man visits other hospitals for severe left tongue pain. Magnetic resonance imaging clearly shows vascular compression of the glossopharyngeal nerve and unclear show of the trigeminal nerve. He was diagnosed with left glossopharyngeal neuralgia and underwent microvascular decompression of the left glossopharyngeal nerve. However, there was no improvement after surgery. During the second surgery in our hospital, microvascular decompression of the trigeminal nerve was performed, in which the trigeminal nerve was fully explored and separated. The patient's pain disappeared after surgery. Finally, the patient was definitely diagnosed with left trigeminal neuralgia. Discussion and Conclusion： Microvascular decompression is currently the most effective surgical option for treating cranial neuralgia. To select patients for microvascular decompression, it will be helpful to have magnetic resonance imaging criteria for identifying true neurovascular compression. However, clinicians should pay more attention to patients' clinical symptoms rather than relying solely on magnetic resonance imaging. It is essential to distinguish between these two diseases. This article aims to improve understanding of the disease, avoid misdiagnosis, and reduce the possibility of secondary damage in patients by reviewing the literature and analyzing cases.